2021
DOI: 10.1021/acs.langmuir.1c02389
|View full text |Cite
|
Sign up to set email alerts
|

A SiO2 Microcarrier with an Opal-like Structure for Cross-Linked Enzyme Immobilization

Abstract: The opal-like SiO 2 microcarriers with different pore diameters named opal-SiO 2 I and opal-SiO 2 II were synthesized and utilized as microcarriers to immobilize Rhizopus oryzae lipase (ROL) and Aspergillus oryzae α-amylases (AOA). ROL and AOA can be more stably immobilized on the cross-linked SiO 2 opals by neopentyl glycol diglycidyl ether (NGDE), which is the first attempt to use it as a cross-linking agent compared with glutaraldehyde. According to the morphology analysis, multiple layers of SiO 2 monodisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Immobilized enzymes dispersed on the porous support surface achieved stabilization for different reasons, stated as follows. Immobilized enzymes get hold of a favorable enzyme environment in porous media, , are recycled over a prolonged period after its separation from the reaction medium, and do not suffer from intermolecular-inactivation processes, which appear either for precipitation or for proteolysis or interaction with external hydrophobic interfaces. , Second, increasing the enzyme rigidity via multipoint covalent attachment ,,,, prevents the subunit dissociation of multimeric proteins ,, that stabilize immobilized enzymes compared to their native form.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilized enzymes dispersed on the porous support surface achieved stabilization for different reasons, stated as follows. Immobilized enzymes get hold of a favorable enzyme environment in porous media, , are recycled over a prolonged period after its separation from the reaction medium, and do not suffer from intermolecular-inactivation processes, which appear either for precipitation or for proteolysis or interaction with external hydrophobic interfaces. , Second, increasing the enzyme rigidity via multipoint covalent attachment ,,,, prevents the subunit dissociation of multimeric proteins ,, that stabilize immobilized enzymes compared to their native form.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most interesting supports for enzyme immobilization is SiO 2 . This inexpensive material, due to its properties such as lack of toxicity, great chemical activity and high porosity as well as the presence of hydroxyl groups onto its surface [17,18], has been widely used for attachment of various enzymes. As was presented by Mondal et al [19], urease immobilized by covalent binding onto a 3D silica gel, retained 100% of its catalytic activity after 30 days, whereas Libertino et al [20] showed that glucose oxidase immobilized onto porous SiO 2 was able to retain its activity even after 3 months of storage.…”
Section: Introductionmentioning
confidence: 99%
“…Various chemical reagents can be applied for carrier modification, such as glutaraldehyde (GA), genipin, glycidol, polyaldehydes, epichlorohydrin, citric acid, sodium tripoly­phosphate (TPP), glyoxal, 1-ethyl-3-(3-(dimethyl­amino)­propyl)­carbo­diimide/ N -hydroxy­succinimide (EDC/NHS), and ethylene­diamine (EDA) . However, these chemical reagents would cause environmental issues and health risks . To address these problems, a green carrier modification strategy is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, these chemical reagents would cause environmental issues and health risks. 9 To address these problems, a green carrier modification strategy is imperative. Mussel-inspired coating is a green and facile carrier modification strategy for covalent enzyme immobilization.…”
Section: Introductionmentioning
confidence: 99%